VIDEO CERITA ANAK BERBASIS TEKNIK VENTRILOQUIST UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA KELAS II SEKOLAH DASAR - Alfa Salsabila Sari; Dwi Agus Setiawan; Denna Delawanti Chrisyarani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a learning media in the form of a children's story video based on ventriloquist techniques and to test its feasibility, practicality, and effectiveness in improving the listening skills of second-grade elementary school students. The background of this study is the low listening skills of students and the lack of use of digital learning media. The media developed is a children's story video entitled "Si Tika dan Sampah Ajaib" which features a hand puppet character named Cici, using ventriloquist techniques and additional animation as a form of story visualization. The study was conducted using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects were 24 second-grade students at SDN Gadang 3, Malang City. In the validation stage, the media was assessed by three experts: a material expert, a media expert, and a language expert. The validation results showed that the media obtained a very high feasibility score, namely 91% from the material expert, 92% from the media expert, and 100% from the language expert, so it was categorized as "very suitable" for use in learning. The practicality test was conducted through a questionnaire to teachers and students. The teacher gave a score of 95%, and the students gave a score of 89%, indicating that this media is very practical to use in the learning process. To test the effectiveness, pretest and posttest instruments were used. The analysis results showed a significant increase in students' listening skills, with an average N-Gain score of 0.8 in the high category and an effectiveness percentage of 82.6% in the effective category. These findings indicate that the developed video media is not only feasible and practical, but also effective in improving students' listening skills.